Penerapan kamus bergambar bahasa mandarin - indonesia terhadap penguasaan kosakata siswa kelas 3 SD Taman Harapan - Valentina, Fellindia Rindi; Afifah, Lilis; Putri, Amira Eza Febrian (Fakultas Sastra, 2023)
Abstrak: The 3rd grade students of SD Taman Harapan have difficulty in learning Chinese vocabulary, causing uneven mastery of Chinese vocabulary among all students in the class. This study aimed to help the students in mastering Chinese vocabulary by applying a Chinese-Indonesian pictorial dictionary and describing students' responses to the application of the dictionary. This research used qualitative descriptive method with two instruments, namely observation sheet and questionnaire sheet. The subjects in this study were 22 3rd grade students of SD Taman Harapan. Data analysis techniques in this study underwent through 6 stages, namely collect the raw data, compiling data for analysis, reading the data, coding the data, interpreting, and presenting data. The results of this study show that the process of applying the Mandarin-Indonesian pictorial dictionary went well. All students are able to follow the learning process actively and conducively, even though they have not known the dictionary before. The application of the Chinese-Indonesian pictorial dictionary received a positive response from students. They claim to have gained ease in learning Chinese by using the dictionary. In addition, students can also study independently by using this Chinese-Indonesian pictorial dictionary. Kata Kunci: kamus bergambar, kosakata, bahasa Mandarin